2021
DOI: 10.1136/bmj.n2231
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and cellular therapies for treatment of covid-19: a living systematic review and network meta-analysis

Abstract: Objective To evaluate the efficacy and safety of antiviral antibody therapies and blood products for the treatment of novel coronavirus disease 2019 (covid-19). Design Living systematic review and network meta-analysis, with pairwise meta-analysis for outcomes with insufficient data. Data sources WHO covid-19 database, a comprehensive multilingual source of global covid-19 literature, and six Chinese databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 81 publications
(131 reference statements)
3
71
1
Order By: Relevance
“…Regarding the main outcome "mortality", the use of IVIG was not associated with a significantly reduced risk of death, independently of COVID-19 severity or type of study (RCT or non-RCT). Such results are in accordance with a recently published living systematic review and network meta-analysis [35].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the main outcome "mortality", the use of IVIG was not associated with a significantly reduced risk of death, independently of COVID-19 severity or type of study (RCT or non-RCT). Such results are in accordance with a recently published living systematic review and network meta-analysis [35].…”
Section: Discussionsupporting
confidence: 92%
“…Antiviral antibodies are effective only very early in COVID-19 disease progression ( 67 ). In later stages of severe COVID-19, patients develop a hyperinflammatory state, which is associated with multiorgan damage and respiratory failure ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In those at risk for progression, clinical trials have found that monoclonal antibodies including ritonavir, casirivimab, imdevimab, bamlanivimab, etesevimab, CT-P59, and sotrovimab were associated with decreased rates of hospitalization compared to placebos; however, only casirivimab-imdevimab was found in a meta-analysis to have moderate certainty evidence for reducing hospitalizations. 20 The combination of nirmatrelvir (SARS-CoV-2 main protease inhibitor) and ritonavir (HIV-1 protease inhibitor and CYP3A inhibitor) has gained emergency use approval by the Federal Drug Administration (Paxlovid, PF-07321332, Pfizer, New York, USA) for use in non-hospitalized patients with COVID-19 at high risk for progressing to severe illness to decrease the risk of hospitalization and death; in the phase 2/3 randomized double blind study, there was an 89% reduction in hospitalization and deaths compared to placebo. 21 In patients with severe or critical COVID-19, metaanalyses have found that glucocorticoids likely reduced the risk of death and mechanical ventilation and duration of hospitalization in admitted patients requiring oxygen support.…”
Section: Mortality and Morbiditymentioning
confidence: 99%
“… 26 In meta-analyses, antiviral antibodies and blood products like convalescent plasma and intravenous immunoglobulins were not associated with a reduction in mortality in those with severe disease. 20 , 27 , 28 The benefits of other treatments like favipiravir, azithromycin, lopinavir-ritonavir, umifenovir are under investigation. 22 …”
Section: Systemic Findingsmentioning
confidence: 99%